Hymenoplasty (Hymen Reconstruction): Sharīʿah Rulings and Applicable Guidelines - El-Sayed Abu El-Ala, Khaled Fouad (Journal of Neonatal Surgery, 2025)
Contemporary surgical operations have made it possible to reconstruct the hymen of a woman who has been forcibly raped, voluntarily engaged in unlawful intercourse, has suffered from hymenal disease, or experienced an accident or direct uterine injury. This medical intervention has raised an issue concerning deceiving the fiancé, as on the wedding night he believes that his wife is a virgin and chaste, whereas the reality is otherwise. Is there an interest in conducting this delicate surgery for the woman whose hymen was ruptured for one of the aforementioned reasons, or is it incumbent upon her to disclose the matter clearly to the fiancé? The present research discusses these issues, highlighting various rulings and applicable guidelines. The element of conservatism is deeply rooted in the people of this beloved homeland, the Kingdom of Saudi Arabia, and if such incidents occur, they are indeed rare. The Saudi governance system, based upon Islamic Sharīʿah, supports every ijtihād (juristic effort) that serves women's interests in accordance with Sharīʿah, scientific, and legal standards. The Research Objectives were summarised as follows: 1.To provide privacy and dignity to women and give them the opportunity to enter into a successful marital life. 2.To compile scattered rulings and regulations related to this issue in one place. 3.To demonstrate the ability of Sharīʿah to offer suitable solutions to contemporary human predicaments. The research has concluded with a number of scientific findings, detailed at the end of the research. It also offered several significant recommendations closely related to the research topic, enumerated at the conclusion.